2022
DOI: 10.3389/fmolb.2022.805887
|View full text |Cite
|
Sign up to set email alerts
|

FAT10 is a Prognostic Biomarker and Correlated With Immune Infiltrates in Skin Cutaneous Melanoma

Abstract: Background: Skin Cutaneous Melanoma (SKCM) is the deadliest cutaneous neoplasm. Previous studies have proposed ubiquitin-like protein FAT10 plays key roles in the initiation and progression of several types of human cancer, but little is known about the interrelation between FAT10 gene expression, tumor immunity, and prognosis of patients with SKCM.Methods: Here, we first performed pan-cancer analysis for FAT10’s expression and prognosis using the Cancer Genome Atlas and the Genotype-Tissue Expression data. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…This is the first study to explore the relationship between UBD and chemoradiotherapy. In a study presented by Yu Wang et al, 33 they found that UBD expression was significantly positively correlated with all analyzed immune cells in skin cutaneous melanoma (B cell, CD8+T cell, CD4+T cell, macrophage, neutrophil, and dendritic cell). In this study, high UBD expression predicted better outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…This is the first study to explore the relationship between UBD and chemoradiotherapy. In a study presented by Yu Wang et al, 33 they found that UBD expression was significantly positively correlated with all analyzed immune cells in skin cutaneous melanoma (B cell, CD8+T cell, CD4+T cell, macrophage, neutrophil, and dendritic cell). In this study, high UBD expression predicted better outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…The TISDB is an online tool for cross-linking studies of tumors and immunity, which contains data from PubMed, The Cancer Genome Atlas (TCGA) and other public databases. 25,26…”
Section: Immune Infiltrationmentioning
confidence: 99%